Real-Time Analytics for Utility Revenue Assurance - Hithesh Seedarla (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Revenue assurance has become a critical priority for modern utility providers as electricity distribution networks grow increasingly complex and data driven. Utilities today operate within highly digitalized environments where large volumes of operational data are generated by smart meters, Advanced Metering Infrastructure (AMI), distribution management systems, and billing platforms [1]– [3]. While these technologies improve operational efficiency and enable real-time monitoring of energy consumption, they also introduce new challenges related to revenue leakage, billing inconsistencies, meter tampering, and energy theft. These issues contribute to significant financial losses and reduce the overall efficiency of utility operations [4], [5]. This paper proposes a real-time analytics framework designed to support revenue assurance in modern power distribution systems. The proposed system integrates streaming data from smart meters, billing databases, transformer monitoring systems, and customer usage profiles to detect anomalies that may indicate revenue loss. A hybrid analytics model combining stream processing, machine learning–based anomaly detection, and risk scoring mechanisms is developed to continuously monitor consumption patterns and billing records [6], [7]. The framework enables real-time identification of irregular consumption behavior, billing discrepancies, and distribution-level energy imbalances. By correlating data from multiple operational systems, the proposed solution allows utilities to detect potential revenue leakage events and prioritize investigation actions. Experimental evaluation using simulated smart meter and billing datasets demonstrates improved detection accuracy and faster response times compared to traditional batch-based monitoring approaches [8], [9]. The proposed approach enhances revenue protection, improves operational transparency, and enables utilities to adopt proactive data-driven revenue assurance strategies within modern smart grid environments.